O lugar da literatura no livro didático de língua portuguesa do ensino médio. - Borges, Antonia Aparecida Pereira (2023)
The present work exposes the results of the research, whose object of study was the didactic collection Portuguese Contemporary: dialogue, reflection and use (2016), by William Cereja, Carolina Dias Vianna and Christiane Damien. The collection is intended for High School and presents the integration of the three curricular fronts - Literature, Language and Language and Text Production, in all chapters. The objective of this work was to investigate to what extent the literary contents of the didactic collection effectively contribute to the formation of the reader. To do so, we used the Theory of Reader Formation, which was presented as a response to our concerns, with regard to the lack of reading habits among Brazilian students, a situation proven by tests and research. We can mention the test carried out by the International Student Assessment Program (PISA), which revealed, in its latest edition, a low performance of Brazilian students in reading. The result, released by the National Institute of Educational Studies and Research Anísio Teixeira (INEP), in 2018, points out that 50% of Brazilian students, aged 15, do not have the basic level of reading. Thus, knowing that the textbook is one of the main tools used in the classroom, we propose a qualitative assessment of its literary grid, since literature constitutes an important resource for school reading practices. We also highlight that, for our theoretical basis, we resorted to scholars who discuss the subject, such as Circe Maria Bittencourt (1993), Marco Antônio Silva (2012), Simone Bueno Borges da Silva and Júlio Neves Pereira (2018), who provide us with major contributions on textbooks in Brazil; Eliana Yunes (2014) is the main theoretical representative of Reader Education in our study, in addition to Marisa Lajolo (1996, 2011), Regina Zilberman (2008) and other authors who corroborate our discussion. It is still necessary to briefly list the main results of the study, which points out: as for the activities proposed by the textbook, it was noticed that the questions are well elaborated and make the student read the texts with the utmost attention. However, in most of the chapters analyzed in the didactic collection, it is noted that there is a predominance of activities of mere verification of reading comprehension, in which the student is oriented only to the copy, without being proposed to this student an authorial and discursive performance. We also noticed that, in most of the chapters analyzed, there is no guidance on the dynamics of the act of reading and we believe that the reading strategy is important in terms of forming a taste for reading. A positive point, perceived in the analysis, is the configuration and arrangement of the contents present in the textbook, since this factor contributes to a better exploration of the didactic contents. In this way, we affirm that, regarding the objective of forming readers, the didactic collection analyzed has several favorable points, however, there is still much to improve. In summary, our work constitutes a reflection tool for all those involved in the process of production and choice of didactic collections.